The Influence of Joben Waterfall Tourism Development on the Socio-Economic Conditions of the Community in Pesanggarahan Village, East Lombok Regency - Imam Syaputra; Diswandi Diswandi; Lukman Hakim (LPPM Sunan Doe, 2023)
This research is about the influence of Joben Waterfall tourism development on the socio-economic conditions of the community. This research aims to analyze the influence of tourism development on the socio-economic conditions of the community around the Joben Waterfall tourist attraction in Pesanggarahan village, Montong Gading sub-district, East Lombok Regency. This research uses quantitative methods with a case study approach. The data collection technique used was distributing questionnaires. The results of this research show that there is a positive impact on the socio-economic as seen from the development of tourism which has an impact on the socio-economic of the community, namely, firstly, the poverty of the respondents has decreased and many other opinions say that the current poverty level is still on the verge of normal, secondly, the respondent's family education has increased, Third, tourism development is able to open up job opportunities for the community by becoming business actors. The negative impact on socio-economics can be seen from the number of traders who experienced a decline, although there were still several respondents who experienced an increase in income, but the number was not comparable to the number of respondents who experienced a decrease in income.